Analysis and coding of visual objects: new concepts and new tools - Sequeira, Manuel Menezes de (1999)
Video coding has been under intense scrutiny during the last years. The published international standards rely on low-level vision concepts, thus being first-generation. Recently standardization started in second-generation video coding, supported on mid-level vision concepts such as objects. This thesis presents new architectures for second-generation video codecs and some of the required analysis and coding tools. The graph theoretic foundations of image analysis are presented and algorithms for generalized shortest spanning tree problems are proposed. In this light, it is shown that basic versions of several region-oriented segmentation algorithms address the same problem. Globalization of information is studied and shown to confer different properties to these algorithms, and to transform region merging in recursive shortest spanning tree segmentation (RSST). RSST algorithms attempting to minimize global approximation error and using affine region models are shown to be very effective. A knowledge-based segmentation algorithm for mobile videotelephony is proposed. A new camera movement estimation algorithm is developed which is effective for image stabilization and scene cut detection. A camera movement compensation technique for first-generation codecs is also proposed. A systematization of partition types and representations is performed with which partition coding tools are overviewed. A fast approximate closed cubic spline algorithm is developed with applications in partition coding.